Effects of ACE inhibition with cilazapril on splanchnic and systemic haemodynamics in man - Gasic, S. (1989)
1 There is recent experimental evidence that the renin-angiotensin-system may play an essential role in producing splanchnic vasoconstriction. However, controversy exists as to the influence of ACE inhibition on splanchnic haemodynamics in man. We therefore investigated whether cilazapril, a structurally new and long-acting ACE inhibitor, interacts with angiotensin I-dependent changes in splanchnic haemodynamics in man, using an experimental model. 2 The effects of cilazapril on angiotensin I-induced splanchnic and systemic haemodynamics were studied in seven normotensive men using the hepatic venous catheter technique (indocyanine-green dye), right-heart catheterisation (thermodilution method), intra-arterial blood pressure monitoring and systolic time-intervals. Dose-responses to angiotensin I were determined under control conditions and 60 min after ACE inhibition with 5 mg oral cilazapril. Angiotensin I was infused intravenously at constant rates in an increasing dose-sequence until systolic blood pressure was greater than 30 mm Hg. 3 ACE inhibition with cilazapril did not change basal splanchnic or systemic haemodynamics to any relevant extent. The angiotensin I dependent increase in systemic and pulmonary resistance and pulmonary capillary wedge pressure was attenuated by cilazapril, as indicated by the shift of the dose-response curves to the right. In the splanchnic vascular bed angiotensin I dose-dependently increased splanchnic vascular resistance and also wedge hepatic venous pressure and decreased splanchnic blood flow. These angiotensin I induced haemodynamic changes were clearly suppressed by cilazapril. The angiotensin I dose needed to produce a 30% increase in splanchnic vascular resistance, given as mean and s.e. mean, was 1.7 ± 0.3 μg min(-1) during control-trials vs 7.3 ± 1.3 μg min(-1) after ACE inhibition with cilazapril (P < 0.001). 4 We conclude that, in man, the influence of cilazapril on acute angiotensin I-mediated haemodynamic responses is present in the splanchnic vascular bed, and that the overall effects of cilazapril are consistent with both arterial and venous effects of the ACE inhibitor. Cilazapril effectively counteracts angiotensin I-induced splanchnic vasoconstriction.